Screening of Solvent Systems for Countercurrent Chromatography Separation of Polar Constituents from Ginkgo biloba L. Seeds - Ruxi Hu; Zhuo Liu; Yi Zhou; Peng Tian; Luqi Li; Zhi Yang; Yatuan Ma (Molecules)
The separation of large polar constituents presents a substantial challenge in natural product research when employing column chromatography techniques, as the process is both complex and time-consuming. In this study, an acetonitrile/tetrahydrofuran/di-(2-ethylhexyl) phosphoric acid/aqueous saturated sodium chloride solvent system was developed and utilized for the countercurrent chromatography of polar constituents from Ginkgo biloba L. seeds. Five polar constituents were effectively isolated using an acetonitrile/tetrahydrofuran/di-(2-ethylhexyl) phosphoric acid/aqueous saturated sodium chloride (2:2:0.8:3, v/v) solvent system using a two-step countercurrent chromatography method. In the initial countercurrent chromatography process, three constituents were successfully purified from the methanol extract: compound 1, compound 4, and compound 5. Compounds 2 and 3, co-eluted from the column, were further subjected to three inner-recycling chromatographic procedures. At last, five constituents were purified and identified, including 4′-O-methylpyridoxine (1); two indole alkaloid N-glucosides, ginkgoside B (2) and ginkgoside A (3); 2-(4-hydroxybenzyl) malic acid (4); and coniferyl alcohol (5). The results demonstrated that the acetonitrile/tetrahydrofuran/di-(2-ethylhexyl) phosphoric acid/aqueous saturated sodium chloride solvent system serves as a feasible system for the efficient countercurrent chromatography separation of polar components.